ANALISIS SMART SYSTEM PELAYANAN JASA TOUR & TRAVEL PAGAR ALAM DENGAN METODOLOGI WARD AND PEPARD - Egy Septian; Nur Ayu Wulantari; Annisa Fitri Aulia; Tata Sutabri (JURNAL ILMIAH BETRIK, 2023)
This research identifies the deficiencies in the information system of Travel Pagar Alam's business operations in the Current Application Portfolio phase. However, in the Future Application Portfolio phase, several recommendations for information systems are proposed to support the sustainability and development of the business in the future using the Ward and Pepard method. From the research findings, the first recommendation in the Strategic Quadrant suggests the use of a Promotional Information System to introduce Travel Pagar Alam to consumers in Palembang through social media platforms such as Facebook, Instagram, Whatsapp, and GoogleAds advertisements. Secondly, in the High Potential Quadrant, the importance of a Web-based Travel Service Information System is emphasized. This system will facilitate consumers with departure schedules, ticket reservations, online payments, and tour package information, all integrated into one platform. Thirdly, in the Key Operational Quadrant, it is recommended to implement an Asset Management Information System to ease the management of travel assets. A cashier system is also recommended to support business transactions in Travel Pagar Alam. Lastly, in the Support Quadrant, the use of simple systems such as Microsoft Word and Excel is suggested to facilitate record-keeping and financial bookkeeping. The research findings indicate that Tour & Travel Pagar Alam has not yet implemented information technology in its business operations. Therefore, a strategic information planning is proposed with recommendations including a web-based tour service information system, a promotional information system, a cashier information system, an asset management information system, and the use of simple systems. It is hoped that the implementation of these recommendations will assist Travel Pagar Alam in selecting and adopting suitable information technology to support its business growth in the future. Research recommendations emphasize the development of the website and company management system for a focus on continuous improvement.